PENGARUH LATIHAN GERAK (STRETCHING) KAKI TERHADAP PENURUNAN NYERI EKSTREMITAS BAWAH PADA LANSIA ARTRITIS REMATOIDDI PANTIWERDHA MOJOPAHIT BRANGKAL MOJOKERTO - Virda Yuniarti, Enny; Kristanti, Dwi (JURNAL KEPERAWATAN SEHAT, 2015)
Physiological changes that happened by the elderly to the various systems in the body of one of the musculoskeletal is rheumatoid arthritis, the most frequent complaints in the elderly that is joint pain in the lower extremities. There are several ways to cope with the pain, one of which is the motion exercises (stretching) feet. This research to determine the effect of motion exercises (stretching) feet to the decline in lower extremities pain in the elderly who suffer from rheumatoid arthritis in nursing homes Mojopahit Mojokerto. The designused wasa pretest-posttest design. Its population is around the elderly who have rheumatoid arthritis with a sample of 11 respondents using purposive sampling techniques and data collection techniques observational pain scale before and aftermotion exercises (stretching) feet. Data processing, inthe test with the Wilcoxon signed rank test. The results showed significant results obtainedα=0.05 which means that H0 is rejected p =0.007 H1 is accepted, which means there is the influence ofmotion exercises (stretching) feet to the decline inlower limbpainin the elderly who suffer from rheumatoid arthritis in nursing homes Mojopahit Mojokerto. Motion exercises (stretching) including the feet in relaxation techniques. Techniques relaxationcan be use as a control discomfort or lower extremitypainin the elderly who suffer from rheumatoid arthritis. Motion exercises (stretching) feet a part to reduce pain can also make the elderly more active.Key words: Elderly, Pain, Stretching.